Diagenetic responses to sea level changes on pleistocene-holocene carbonates in the Celebes Sea, East Sabah, Malaysia - Syazwani, N. (European Association of Geoscientists and Engineers, EAGE, 2013)
Limestones are particularly susceptible to drastic early diagenetic modifications, either during or shortly after deposition or during periods of subaerial exposure. Tracing the depth to which the vadose zone penetrated along the sea level notch-opening and combining petrographic results, stable isotope data and carbon-14 dating, studies from the limestones, i.e. beachrock, marine hardground and elevated reef limestone in the Celebes Sea, east of Sabah, Malaysia suggest that the sea level fluctuated approximately â¼ 1.0 m above/below modern MSL in Holocene. Blocky calcite mosaic with meniscus fabric from elevated reef islands that have been already exposed between 32, 845 and 20, 770 years BP, gives depleted values for Î´18O and Î´13C, suggesting a mixing between an original signature and a soil-derived meteoric signature and meteoric water in origin. The formation of beachrock at the intertidal zone between 3, 840 to 2, 660 years BP, with meniscus fabric of aragonite cement, confirmed this interpretation. Copyright Â© (2012) by the European Association of Geoscientists & Engineers All rights reserved.